2015
DOI: 10.1002/cae.21634
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid cloud service selection strategy: Model and application of campus

Abstract: The paper proposes hybrid cloud service selection optimization scheme. Hybrid cloud service selection optimization is distributed to and performed at two levels: hybrid cloud user agent-hybrid cloud service agent at hybrid cloud service layer and hybrid cloud service agent-hybrid cloud agent at hybrid cloud resource layer. Interactions among hybrid cloud user agent, hybrid cloud service agent, public cloud agents and private cloud agents are mediated by means of market mechanisms. Two level hybrid cloud servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Peng et al (2015) indicated that task scheduling is the necessary prerequisite for performance optimization and resource management in the cloud computing system. Interactions among hybrid cloud user agent, hybrid cloud service agent, public cloud agents, and private cloud agents are mediated by means of market mechanisms (Li, 2015).…”
Section: Theoretical and Practical Review Of The Literaturementioning
confidence: 99%
“…Peng et al (2015) indicated that task scheduling is the necessary prerequisite for performance optimization and resource management in the cloud computing system. Interactions among hybrid cloud user agent, hybrid cloud service agent, public cloud agents, and private cloud agents are mediated by means of market mechanisms (Li, 2015).…”
Section: Theoretical and Practical Review Of The Literaturementioning
confidence: 99%